2023
DOI: 10.3390/tropicalmed8030153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 Severity and Mortality Rates in the First Four Epidemic Waves in Hungary in a Single-Center Study with Special Regard to Critically Ill Patients in an Intensive Care Unit

Abstract: Different variants of coronavirus 2 (SARS-CoV-2), a virus responsible for severe acute respiratory syndrome, caused several epidemic surges in Hungary. The severity of these surges varied due to the different virulences of the variants. In a single-center, retrospective, observational study, we aimed to assess and compare morbidities and mortality rates across the epidemic waves I to IV with special regard to hospitalized, critically ill patients. A significant difference was found between the surges with rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was found that the course of the disease in patients from the 3 rd COIVID-10 wave, infected with the transformed alpha (B.1.1.7) variant, was significantly more severe than in the previous ones. 13,14 The subsequent 4 th wave, comprising the next variants of SARS-CoV-2-Delta (B.1.617.2), resulted in a more severe course of the disease, being the most dangerous and having the worst results. 15,16 However, differentiation of SARS-CoV-2 viral variants was also not common in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the course of the disease in patients from the 3 rd COIVID-10 wave, infected with the transformed alpha (B.1.1.7) variant, was significantly more severe than in the previous ones. 13,14 The subsequent 4 th wave, comprising the next variants of SARS-CoV-2-Delta (B.1.617.2), resulted in a more severe course of the disease, being the most dangerous and having the worst results. 15,16 However, differentiation of SARS-CoV-2 viral variants was also not common in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Since the official recognition of SARS-CoV-2 in January 2020 [1], a significant number of studies have been published, elucidating the characteristics, diagnosis methods, possible mechanisms, and severity of the disease, as well as immune responses to SARS-CoV-2 in people suffering from COVID-19 and information on the virus itself [4][5][6][7][8][9][10][11]. However, these studies largely focused on COVID-19 s ability to cause deadly disease in humans.…”
Section: Introductionmentioning
confidence: 99%